Executive Functions in Chronic Mesial Temporal Lobe Epilepsy. (23rd January 2011) - Zamarian, Laura; Trinka, Eugen; Bonatti, Elisabeth; Kuchukhidze, Giorgi; Bodner, Thomas; Benke, Thomas; Koppelstaetter, Florian; Delazer, Margarete
Abstract : There is no consensus as to whether mesial temporal lobe epilepsy (MTLE) leads to executive function deficits. In this study, we adopted an extensive neuropsychological test battery and assessed different executive functions in chronic, unilateral MTLE. Performance of MTLE patients was compared with that of healthy peers and with normative data. Several MTLE patients had scores below cut-off or below the 10th percentile of normative data. Scores of the whole patient group were overall in the average range of normative data. Relative to controls, MTLE patients performed poorly in tests of working memory, cognitive flexibility, categorical verbal fluency, set-shifting, categorization, and planning. These findings raise an important methodological issue as they suggest that executive function deficits in chronic MTLE may be individually variable and that their assessment should include different tests. Deficits in chronic MTLE are not limited to temporal lobe functions, such as memory, but may extend to extra temporal cognitive domains, such as executive functions.